Elementary School Teachers’ Reflections on Shy Children in the Classroom - Bosacki, Sandra Leanne; Coplan, Robert J.; Rose-Krasnor, Linda; Hughes, Kathleen (Alberta Journal of Educational Research, 2011)
This study explored teachers’ perceptions of shy children in the classroom during the elementary school grades. Seven teachers (1 male, 6 female) from elementary schools located in geographically diverse areas of Canada participated in semistructured telephone interviews that explored their perceptions of and experiences with shy children in the classroom. Transcripts were analyzed for emerging themes about teachers’ conceptions of shy children and teacher-shy child interactions. Findings suggest that shyness and social communication may influence elementary schoolteachers’ classroom practices and the teacher-child relationship. Teachers’ roles in shy children’s socio-emotional functioning and academic success are discussed. Cette recherche a étudié les perceptions qu’ont les enseignants au primaire des enfants qui sont gênés. Sept enseignants (1 homme, 6 femmes) d’écoles primaires situées dans des zones géographiquement diverses au Canada ont participé à des entrevues téléphoniques semi-structurées portant sur leurs perceptions des enfants gênés et leurs expériences avec eux en salle de classe. Nous avons analysé les transcriptions pour en dégager des thèmes sur les conceptions qu’ont les enseignants d’enfants gênés et les interactions entre les enseignants et les enfants gênés. Les résultats indiquent que la gêne et la communication sociale pourraient influencer les pratiques des enseignants au primaire et leur rapport avec leurs élèves. Nous discutons des rôles des enseignants dans le fonctionnement socio-émotionnel des enfants et dans la réussite académique.